Avaliação da água disponível no solo utilizando diferentes pontos de tensão na curva de retenção de água - Braga, Elton Dannilo Carvalho (Universidade Federal Rural do Semi-Árido, 2020)
In recent years, Brazilian agriculture has undergone profound changes, these changes occurred through plant breeding, chemical and biological pest control, modernization of agricultural machinery and especially in the use of irrigation systems. These changes enabled the expansion of agricultural areas and brought major productivity gains crops. It is essential for correct sizing and planning of irrigation knowledge of water retention characteristic curve in the soil. This curve is related to the soil moisture tension with which the water is retained. This study aims to evaluate the achievement of the water retention curve through the mathematical model proposed by van Genuchten (1980). Thirty were analyzed and five groups size tension equal to five for Ap and B22 horizons for soil samples with deformed and undeformed structure, where θr parameters were estimated θs, α or with the aid of the Solver tool a supplement Microsoft Excel for calculating nonlinear equations through interactions calculation. The tensions that best fit the model were evaluated by the mean square deviations (MSD). It was found that: (a) the choice of tensions influenced the amount of water available in the soil, increasing or decreasing its value. (b) the absence of tension of 1.5 MPa to obtain the water retention curve changes the amount of water available in the studied horizons. (b) tension 0.0005; 0.001; 0.006; 0.033 and 1.5 MPa showed the best fit to the horizon Ap the deformed structure; (c) tension 0.0005; 0.006; 0.01; 0.07 and 1.5 MPa showed the best fit to the horizon Ap the undeformed structure; (d) tension 0.0005; 0.01; 0.033; 0.07 and 1.5 MPa showed the best fit to the horizon B22 deformed structure; (e) tension 0.001; 0.003; 0.006; 0.01 and 1.5 MPa showed the best fit to the horizon B22 undeformed structure. The results show that there is possibility of constructing the water retention curve with a reduced amount of stress values.
Keywords: Agricultura; irrigação; curva de retenção; água disponível; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA